Visual Metaphor of Javanese Cartoon: The Interpretation of Cultural Socio-Politic in Goenawan Pranyoto’s Comic Cartoon Mbeling “Ande Ande Lumut” (1951-2014) - Thalhah, Abdullah Ibnu (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2016)
A comic cartoon is a communication media that is widely enjoyed and accepted by people. As a literary and journalistic work, the comic cartoon also captures the surrounding cultural situation. The modern and traditional cultural sign, fact and imagination, realist pattern and cartoon or caricature are used in a combination that seems contra versed (it is called double code discourse in postmodernism discourse), to show metaphor pattern relationship. The metaphor is applied through the transformation and play of the signs in the past and the future. They were spread, combined, and also transformed as a tool to show the creator’s expression. In this research, it was found that there was a very close relationship between the use of metaphoric signs and Indonesia’s social-politic situation in 1983. On one hand, Metaphor in comic cartoon Mbeling was a tool created to insinuate and criticize the corrupt and feudal Orde Baru authoritarian. It insinuated the violence involving the government officers in every aspect of the people’s life. On the other side, the comic cartoon also becomes the representation of contemporary Javanese culture that was open to other culture and acculturation.